Colostrum supplementation with n-3 fatty acids alters plasma polyunsaturated fatty acids and inflammatory mediators in newborn calves - Opgenorth, Julie (J Dairy Sci, 2020)
Calves may experience increased oxidative stress at birth through activation of metabolic and respiratory processes. Reducing oxidative stress may enhance calf viability in early life. Our objective was to determine the dose response to fish and flaxseed oil when supplemented in colostrum on concentrations of plasma fatty acid (FA), FA metabolites, and index of oxidative stress during the critical first week of life in calves to understand how supplementing n-3 FA may decrease oxidative stress. We hypothesized that n-3 FA supplemented in colostrum in a linear dose-dependent fashion would associate with increased plasma n-3 FA concentrations and decreased oxidative stress. Twenty-four male and female Holstein calves were randomly assigned to receive 0, 30, 60, or 120 mL of a 1:1 fish to flaxseed oil supplement in colostrum. All calves received 2.8 L of previously frozen colostrum (≥22% Brix) with their respective treatment within 6 h after birth. Blood was sampled before first feeding after birth and on d 1, 2, 4, 7, and 14 d of age to assess oxidant status and plasma free PUFA, phospholipid FA, and oxylipid concentrations. Health indicators were observed daily. Indicators of general health and growth were unaffected by treatment. Supplemented calves exhibited greater concentrations of n-3 FA in plasma as free and phospholipid FA and some n-3 and n-6 FA-derived oxylipids in the first week of life in a linear fashion with increasing supplemental dose. Fish and flaxseed oil treatments did not alter oxidant status but overall decreased isoprostane concentrations in plasma, indicating oxidative stress was decreased. Together, these responses indicate that the fish and flaxseed oil supplement was antiinflammatory. In conclusion, supplementing colostrum with 30, 60, and 120 mL of a 1:1 mixture of fish and flaxseed oil linearly increased plasma concentrations of n-3 FA and metabolites and decreased biomarkers of oxidative stress, but did not alter oxidant status or affect health or growth. Our findings suggest neonatal calves may benefit from n-3 FA supplementation in colostrum to encourage a greater antiinflammatory state.